A CASE CONTROL STUDY OF TILKALKA (SESAMUM PASTE) MADHUSARPIVARTI IN THE MANAGEMENT OF VIDRADHI BHEDANA AND VISTRAVANA (I & D) - V. Shekokar, Anantkumar; M. Borkar, Kanchan; U. Sapkal, Lakshman (International Journal of Ayurveda and Pharma Research, 2015)
The diseases Vidradhi (abscess) is a common ailment irritating humankind and incapacitate the sufferer for his routine work. The primary aim of the treatment was to give an effective and safe surgical approach to this perplexing problem. The healing of wound formed after I & D still remains a major problem to the surgeon as well as to the patient. Though systemic action of drugs are in prevalence, satisfactory local management still remains a pipe dream. Routinely in modern surgical practice H2O2 (Hydrogen peroxide) and Betadine is commonly used for cleaning and debridement of I&D wound. H2O2 produces heat when come in contact with tissues and disturb the newly formed granulation tissue which decreases wound healing rate. An attempt was made at the proper understanding of the historical aspect of Vidradhi Chikitsa (treatment), its etiopathogenesis, methodology of wound healing after I & D both in the light of Ayurvedic and modern knowledge. So present study reveals efficacy of Tilkalka (sesamum paste) madhusarpi Varti w.s.r. to Vidradhi after its Bhedan and Vistravana (I&D) procedure. The case control study was conducted on which randomly selected 2 patients and divided in 2 groups 1st is control group treated with H2O2 and Betadine, 2nd is trial group treated with Tilkalka madhusarpi Varti. The clinical assessment was done on the basis of grading criteria with basic symptomology of Vidradhi after I&D like pain, local temp, discharge, colour and smell. Then mean scores levels of these symptoms before and after the treatment of 2 groups were done & final conclusion was obtained.